A cephalometric evaluation of the Filipino patients aged 13 to 29 years old using the downs analysis - Fathi, Abbas
The aims of this study were to comprehensively evaluate the cephalometric features of Filipinos using the Downs Analysis. The study population consisted of 70 lateral cephalograms (male = 14, female = 56) from the Graduate Program in Orthodontics, U.P. College of Dentistry. Age of these patients ranged from 13 to 29 years with a mean age of 21.5 years. Cephalometric analysis was made on tracing sheets using the ten skeletal and dental parameters of Downs. Statistical analysis was done using the Statistical Analysis for Social Sciences Version 10. Unpaired t-test was applied for the significant difference between genders. Comparative statistics were also performed to verify ethnic differences among the Filipino, Caucasian, Negro (Altemus) and Chinese (Cantonese) groups. Results revealed the following: there were no significant differences in all skeletal and dental parameters between the Filipino male and females groups, except for the y-axis values. Statistically, the Filipino male had a significantly larger Y-axis than its female counterpart. The mean skeletal values obtained showed that the Filipinos tend to have a retrusive mandible, protrusive maxilla and a steep mandibular plane. Over all the dental patterns of the Filipinos group showed the smallest interincisal angle among the four groups. Due to the more proclined upper and lower incisors, a predominance of bi-maxillary protrusion can be anticipated in the Filipino group. The Filipino group also showed the flattest occlusal plane among the four racial groups. When the overall findings were evaluated, it could be concluded that the Filipinos tended to have a convex profile and bi-maxillary protrusion due to the protrusiveness of the upper and lower incisors.